Exploring the Antecedents of Customer Loyalty in the Malaysian Retail Sector - Sany Sanuri Mohd Mokhtar; Maha Mohammed Yusr (International Review of Management and Marketing, 2016)
As the market is becoming more competitive, managers and marketers are becoming more aware of the importance of being a customer-oriented company to survive, and in this regard, customer loyalty is one of the major outcome of customer-oriented approach. Moreover, shifting the concept of marketing exchange from transactions to relationship emphasizes the importance of building customer loyalty. Therefore, nowadays, marketers are in the quest to obtain knowledge on how to build customer loyalty. However, most of the previous studies focused on business to customer (B2C) context. Due to several differences between B2C and B2B, there is a need to investigate the antecedents of customer loyalty separately from B2C. Therefore, this study focused on the Malaysian retail sector. The obtained results supported a positive influence of each of four adopted constructs, which represented by service quality, corporate image, customer trust, and customer switching cost, on customer loyalty. In light of the findings, several managerial implications were highlighted.